Glycopolymers : Synthesis and Applications. - Narain, Ravin (Smithers Rapra, 2014)
Glycopolymers have received considerable interest in recent years due to their increasing potential applications in material science and biomedicine. With better understanding of the role of carbohydrates in biological systems and with recent advances in organic and carbohydrate chemistry, the design and synthesis of glycopolymers have become simpler where significant research efforts have been carried out towards the fabrication of advanced glyco-polymeric architectures for improved performance. This book provides an update on the recent advances on the synthesis of glycopolymers, their chara.